Clinical outcomes of surgically resected combined small cell lung cancer: a two-institutional experience - Zhang, Chao; Yang, Haitang; Zhao, Heng; Lang, Baoping; Yu, Xiangdong; Xiao, Peng; Zhang, Xiao (Journal of Thoracic Disease, 2017)
Background: The combined small cell lung cancer (c-SCLC) was rare and its clinicopathological characteristics had not been thoroughly described. The aim of this study was to determine prognostic factors and survival in c-SCLC patients. Methods: Clinical records of patients with c-SCLC who underwent surgery between January 2009 and December 2013 in two institutions were retrospectively reviewed. Results: Ninety-seven patients were identified. The most common pathology was combined SCLC and large cell neuroendocrine carcinoma (LCNEC, N=46), followed by combined SCLC and squamous cell carcinoma (SCC) (N=32), combined SCLC and adenocarcinoma (AC) (N=12), and combined SCLC and adenosquamous carcinoma (ASC) (N=7). The overall survival (OS) rates of the entire cohort were 42.4% and 35.2% at 3 and 5 years, respectively. Multivariate analysis identified sex [female vs. male, hazards ratio (HR) =0.38; 95% confidence interval (CI): 0.19–0.79; P=0.010], age (53 years, HR =0.28; 95% CI: 0.09–0.81; P=0.019), performance status (2, HR =0.08; 95% CI: 0.02–0.32; P